Interleukin-17 Can Induce Osteoarthritis in Rabbit Knee Joints Similar to Hulth's Method. (26th July 2017) - Wang, Zili; Zheng, Chenhuang; Zhong, Yunbin; He, Jinshen; Cao, Xu; Xia, Hansong; Ba, Hongliang; Li, Pei; Wu, Song; Peng, Cheng
Abstract : Interleukin-17 (IL-17) is closely related to osteoarthritis (OA), but animal studies that employ IL-17 to induce OA are currently lacking. Therefore, this study evaluated the effect of IL-17 in the rabbit knee joint. The right knees served as the control group. The left knees were divided randomly into 4 groups: a Hulth group and 3 IL-17 groups (1-ng, 10-ng, and 50-ng groups). OA was induced in the Hulth group using Hulth's method. The IL-17 groups were injected with 1, 10, or 50 ng of IL-17 as indicated. Specimens were collected at 72 h, 1 week, 3 weeks, 6 weeks, and 12 weeks after surgery or the last injection. Subsequently, the following experiments were conducted: X-ray analysis, histological evaluation, and polymerase chain reaction (PCR) analysis of the mRNA expression levels of cartilage degeneration-related markers. At 12 weeks, like the Hulth group, the 10-ng and 50-ng IL-17 groups displayed typical manifestations of OA. The X-ray results, histological scores, and mRNA expression levels showed statistically significant differences between the control group and the 10-ng and 50-ng IL-17 groups. In sum, injecting 10 ng of IL-17 into the rabbit knee joint can induce OA similar to OA induced by Hulth's method.